The Effectiveness of the Problem-Based Learning Model in the Subject of Facilities and Infrastructure for Students - Aripahartati Devi; Risma Niswaty; Sirajuddin Saleh (ASHA Publishing, 2025)
21st-century learning heavily emphasizes critical thinking, collaboration, and problem-solving skills. Therefore, teachers must implement appropriate steps to meet these criteria. One alternative that can be implemented is through the application of a problem-based learning model. This study is intended to determine the effectiveness of the problem-based learning model, especially in the subject of facilities and infrastructure in class XI MPLB I. The study employs a qualitative approach that utilizes descriptive research methods. The data collection techniques used include observation, interviews, and documentation. The results of the study show that problem-based learning is effective in four main indicators, namely: 1) student involvement in learning is good, shown by active attention, participation in asking questions, and the ability to answer teacher evaluations; 2) inquiry and investigation are effective even though students still face several obstacles; 3) student performance in doing assignments shows a good understanding of the material; and 4) reflection on problem solving goes well through teacher evaluation and guidance in correcting students' mistakes. In addition, this study identifies supporting factors such as adequate learning facilities, learning motivation, teacher competence, and a conducive classroom atmosphere. As for the inhibiting factors, there are limitations in study time and differences in academic ability between students. The application of the problem-based learning model can increase students' activeness, understanding, and critical thinking skills if implemented optimally with the support of adequate internal and external factors.